2004
DOI: 10.1152/ajpheart.00101.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of natriuretic peptides in regulation of conduit artery distensibility

Abstract: Arterial distensibility, assessed by the pulse-wave velocity (PWV), is an independent predictor of cardiovascular risk. We investigated whether natriuretic peptides, acting locally, modify conduit artery distensibility in vivo. All studies were conducted in anesthetized sheep (n = 18) by using a validated ovine hindlimb model. In brief, the PWV was calculated, with the use of the foot-to-foot methodology, from two pressure waveforms recorded simultaneously with a high-fidelity dual pressure-sensing catheter pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…A number of circulating and endothelium-derived factors, including nitric oxide influence large artery stiffness. 23,24 Inflammation is associated with endothelial dysfunction, which may lead to functional stiffening of the large arteries due to reduced nitric oxide bioavailability and increased activity of opposing mediators such as endothelin-1. 25,26 Endothelial dysfunction may lead to a number of changes in the extracellular matrix including smooth muscle cell proliferation and increased synthesis of structural proteins including collagen as well.…”
Section: Discussionmentioning
confidence: 99%
“…A number of circulating and endothelium-derived factors, including nitric oxide influence large artery stiffness. 23,24 Inflammation is associated with endothelial dysfunction, which may lead to functional stiffening of the large arteries due to reduced nitric oxide bioavailability and increased activity of opposing mediators such as endothelin-1. 25,26 Endothelial dysfunction may lead to a number of changes in the extracellular matrix including smooth muscle cell proliferation and increased synthesis of structural proteins including collagen as well.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that a number of circulating and endothelial-derived factors, including nitric oxide and endothelin-1, influence large artery stiffnessproviding so-called 'functional' regulation of arterial stiffness. [33][34][35] Inflammation is associated with endothelial dysfunction, 11,28 which may lead to functional stiffening of the large arteries due to reduced nitric oxide bioavailability and increased activity of opposing mediators such as endothelin-1. Such a mechanism may also explain why acute vasculitis is potentially associated with reversible stiffening.…”
Section: What Does the Study By Duprez Et Al Add?mentioning
confidence: 99%
“…Several studies demonstrated that inflammation is considered the major cause of endothelial dysfunction and arterial stiffening in both patients' groups. C-reactive protein (CRP) and some of circulating and endothelium-derived factors, including nitric oxide, von Willebrand factor (vWF), excess of adhesive molecules, endothelin-1 may influence the elasticity of large arteries providing so-called "functional" regulation of arterial stiffness (12)(13)(14). Not only active chemical compounds but also disease itself may harm endothelium and induce arterial stiffening.…”
Section: Introductionmentioning
confidence: 99%